Does financial cooperation agreement influence the real economy?: A GMM panel data approach on ASEAN+3 countries - Rahman, Md. Saifur; Aslam, Mohamed; Lau, Wee Yeap; Shahari, Farihana (2015)
This study aims to investigate the influences and contributions of financial integration on real sectors in ASEAN+3 economies. It employs General Methods of Moment (GMM) technique and uses the proxies of financial integration and real economy from 1990 to 2012. The findings show that financial integration on real economy has positive effect, such as increasing government spending, reducing unemployment, and so forth. The finding has great implications for the regional economies. It is recommended that the policy makers improve the financial integration in order to develop the real economy.